Assessing Self-Reported Competence Among Registered Nurses Working as a Culturally Diverse Work Force in Public Hospitals in the Kingdom of Saudi Arabia. (January 2021) - Halabi, Jehad O.; Lepp, Margret; Nilsson, Jan
Introduction: Nurses in the Kingdom of Saudi Arabia (KSA) represent a multicultural workforce who are educated in different countries from around the world. The purpose was to assess professional competence among a multicultural workforce of registered nurses in KSA in relation to individual and work-related factors.Method: The Nurse Professional Competence Scale was used in a cross-sectional design.Results: Registered nurses ( N = 541) reported highest scores for "nursing care, " and "value-based nursing care, " and lowest scores for "care pedagogics, " and "development, leadership, and organization of nursing care." All CAs achieved 0.80 or more Cronbach's alpha. Known-group validity was verified by comparing nurse managers and staff nurses competence in organization, administration, and leadership of nursing care ( p = .000).Discussion: There is room for competence development in care pedagogics, and development, leadership, and organization of nursing care. Assessing registered nurses competence is of importance for planning and implementing cultural congruent nursing care.